BETWEEN MULTICULTURAL AND INTERCULTURAL CONCEPTS: EDUCATION FOR MEMBERS OF NATIONAL MINORITIES IN SERBIA: Education for members of national minorities in Serbia - Nenadić, Danijela (Political Review, 2025)
Education for members of national minorities represents one of the most important topics in contemporary political theory with a specific attention dedicated to concepts of multiculturalism and interculturalism as reality in most of ethnically diverse societies. In such societies, the protection of minority rights becomes a key indicator of democratic maturity, integration and social cohesion, which makes education a crucial factor for accomplishing and maintaining political stability. Albeit the fact that there is no universal model of successful education for national minorities, high level of international standards and mechanisms guide  the  preservation of linguistic and cultural rights of  minorities.  At  the theoretical level, liberal political thought views education as a form of soft power essential for democratic development. Interculturalism is often seen as a dynamic exchange between cultures and thus, more effective than sole multicultural coexistence,  as it requires genuine dialogue, acceptance and solidarity. In the past 25 years, Republic of Serbia has developed a unique legal and institutional framework for minority  protection  and  for  the  preservation  of education for minorities through domestic legislation, ratification of international documents and special institutional mechanisms. Despite this, challenges in implementation remain, highlighting the  need  for  continues  policy  improvement   to ach ieve the proclaimed ideal of interculturalism. Contemporary theorists such as Kymlicka, Talyor and Bennett emphasize the crucial role of education in safeguarding collective identity, language and culture, as well as fostering interethnic dialogue and social cohesion. The main aim of modern debates    is to reach the fine line and find a balance between minority identity preservation and integration into wider society, navigating between multicultural and intercultural models. The system designed in Serbia offers three different models of minority education: full instruction in minority language, instruction in Serbian with minority language and culture as subjects and bilingual education (in Serbian and minority language). The first model prevails in practice, but faces various obstacles and challenges, such as lack of qualified teachers, textbook, financial resources and complex procedures. In Serbia (and in many other Western Balkan countries) educational reforms reflect a gradual shift from ethnocentric models toward intercultural approaches. Educational policies are designed to cultivate solidarity and understanding, reduce ethnic distance and strengthen the feeling of belonging. Overall, the paper underscores that quality minority education is indispensable for democratic governance, successful diversity management and societal stability. It argues that the way forward for Serbia is within strengthening intercultural educational policies and practical implementation, with the main aim of upholding identity differences while promoting shared belonging and inclusive citizenship. The paper is primarily based on a theoretical approach and a descriptive analysis of relevant scientific literature, statutory and bylaw acts, as well as research in the field of public education and national minorities.
Keywords: educational policies; education of national minorities; multiculturalism; interculturalism; social cohesion